Ekopedagogi sebagai Fungsi Praksis Imago Dei dalam Menjaga dan Merawat Lingkungan - Agustin Soewitomo Putri (STT Iman Jakarta, 2022)
The world is in a state of environmental crisis, disaster, and various problems that touch the interests of many people's lives. In this case, the Bible reveals that likeness to God is a form of responsibility to deal with this problem. In God's likeness, there is a mandate and responsibility for caring for nature to the next generation. One of the implementations that can be carried out is through eco-pedagogy. The world, which is entering the era of society 5.0, is pulling humanity forward in a technological development that cannot be avoided, and preserving the environment is a generational educational task that affects the comfort of the